Comparison of the Effectiveness of Unified Transdiagnostic Treatment and Compassion-Based Approach on Suicidal Ideation and Spiritual Well-Being in Women Victims of Domestic Violence - Hossein Alizadeh , Mahboobe; Ghamari , Mohammad; GholamiTooranposhti , Marzieh (Applied Family Therapy Journal (AFTJ), 2025)
Objective: The present study aimed to compare the effectiveness of Unified Transdiagnostic Treatment and the Compassion-Based Approach on suicidal ideation and spiritual well-being in women victims of domestic violence.Methods: This study is applied in terms of its purpose and quasi-experimental in nature and method, utilizing a pre-test, post-test, and two-month follow-up design with a control group. The study population comprised all women victims of domestic violence who sought help from social emergency centers and family counseling clinics in Tehran during the second half of 2023. The sample consisted of 51 participants who were selected through purposive sampling and randomly assigned to experimental and control groups. The first experimental group received an eight-session (90-minute each) Compassion-Based Therapy intervention program, while the second experimental group received a ten-session (60-minute each) Unified Transdiagnostic Treatment program at these centers. The control group did not receive any intervention. Data collection tools included the Violence Against Women Questionnaire by Haj-Yahya (2001), the Beck and Steer Suicidal Ideation Scale (1991), and the Spiritual Well-Being Scale by Paloutzian and Ellison (1982). The obtained data were analyzed using repeated measures analysis of covariance (ANCOVA) and Bonferroni post hoc test with SPSS 27 software.Findings: The study findings indicate that both Compassion-Based Therapy and Unified Transdiagnostic Treatment led to a reduction in suicidal ideation and an increase in spiritual well-being in the experimental groups. Additionally, considering the mean difference, Unified Transdiagnostic Treatment had a greater effect than the Compassion-Based Approach in reducing suicidal ideation and enhancing spiritual well-being (p < .05).Conclusion: Based on the findings of this study, Compassion-Based Therapy and Unified Transdiagnostic Treatment are effective approaches for improving spirituality and reducing suicidal ideation in women victims of domestic violence. Psychologists and family specialists are encouraged to utilize these findings to enhance the quality of family life.